Pilipino translation of selected stories about children from other lands for story reading in the lower primary grades - Medrano, Zosima S. 1944- (1974)
In this study, ten picture story books about children from Japan, China, India, America, France, Tibet, Thailand, Spain and Russia were translated in Pilipino for the benefit of children in the lower primary grades. The stories are presented in picture book form and are designed to broaden, deepen and elevate the children's reading tastes. Each story is followed by critical thinking questions for the students.
Thesis (M.A.T.)--University of the Philippines
Keywords: Children's literature -- Study and teaching